Development of rice husk ash-based geopolymer binder for fire resistant coating - Mohd Basri, Mohd Salahuddin (2016)
Despite the growing popularity of geopolymer in various industrial applications, the literature showed gaps on understanding of factors influential on the properties of geopolymer binder (GB). The main objective of this research is to develop an eco-friendly rice husk ash (RHA)-based GB material suitable as fire resistant coating and panel materials for building construction. Four experiments were conducted; namely fire resistant, compression, flexural, and adhesion tests. Fractional factorial design (FrFD) and response surface methodology (RSM) were used to design the experiments incorporating five factors; namely ratio of activated alkaline (AA) solution, RHA to AA (RHA/AA) ratio, curing temperature, curing time, and sodium hydroxide concentration and analyze their interrelationship and effect on GB properties. The optimum range for GB composition was accordingly determined using superimposed contour plotting. Results showed that RHA/AA ratio was the most influential factor on all GB properties (thermal, mechanical, and physical properties). RHA provided effective fire resistant properties since its GB coating exhibited intumescent-like expansion. The newly developed formulation of GB which exhibited semi-brittle behavior was able to produce good fire resistance and compressive strength properties. In addition, good adhesion and flexural properties were important in providing coating with good fire resistant properties. Optimal GB panels were formulated at W/S and Si/Al ratios of 1.05 to 1.13 and 95 to 110, respectively while optimal GB coating formulated at W/S and Si/Al ratios of 110 to 130 and 1.20 to 1.33, respectively. RHA proved to be the best alternative aluminosilicate source and the RHA-based GB, when used as panel or coating materials, can potentially improve fire safety in building construction.